2023
DOI: 10.1021/acsapm.2c01731
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Route to Fabricate Ultralong and Uniform Polypyrrole Nanowires with High Electrochemical Capacitance for Supercapacitor Electrodes

Abstract: This work demonstrated a straightforward strategy to fabricate ultralong interconnected polypyrrole (PPy-GS) nanowires with a gemini surfactant (GS) as a soft template and dopant. Pure PPy particles and a PPy nanowire doped with CTAB (PPy-CTAB) were prepared for comparison. The results showed that the electrochemical performances, conductivity, and morphology of PPy-GS could be significantly changed by changing the concentration of GS in the aqueous phase owing to the different self-assembly behaviors. When th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 69 publications
(128 reference statements)
0
6
0
Order By: Relevance
“…Additionally, regarding the electrostatic force that might have occurred from Fe + between particles, as mentioned above [ 54 , 55 ], this interaction force may disrupt sheet-like forming and increase porosity in the PPy structure [ 59 ]. Some works reported that a specific higher porous PPy structure represented a higher surface area and an increase in its electronic properties [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, regarding the electrostatic force that might have occurred from Fe + between particles, as mentioned above [ 54 , 55 ], this interaction force may disrupt sheet-like forming and increase porosity in the PPy structure [ 59 ]. Some works reported that a specific higher porous PPy structure represented a higher surface area and an increase in its electronic properties [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Figure 3, the Nyquist plots of PPy-based electrodes showed different spectral representations in different electrolytes. Semicircles were present in the high frequency region, indicating the charge transfer process taking place between the working electrode and the electrolyte [52]. Straight lines of varying slopes were seen in the low frequency region, referring to the diffusion of charges/ions in the electrodes [52,53].…”
Section: The Frozen-state Polymerized Ppy With Dyes and Its Capacitiv...mentioning
confidence: 97%
“…Semicircles were present in the high frequency region, indicating the charge transfer process taking place between the working electrode and the electrolyte [52]. Straight lines of varying slopes were seen in the low frequency region, referring to the diffusion of charges/ions in the electrodes [52,53]. Here, PPy-MO had the least charge transfer resistance, R ct (see Table S3), in all electrolytes, indicating its good conductivity, and then, it was succeeded by PPy-AB and PPy-FS.…”
Section: The Frozen-state Polymerized Ppy With Dyes and Its Capacitiv...mentioning
confidence: 99%
“…Researchers are focusing their efforts on developing active electrode materials with superior electrochemical stability, a large specific area, and a quick ion and electron diffusion rate to improve the storage mechanism of supercapacitors. [9][10][11] In recent years, transition metal hydroxides, [12][13][14] oxides, [15][16][17][18][19] and conductive polymers [20][21][22] have been widely employed for energy storage applications. [23,24] In comparison to the other materials, transition metal hydroxide/ oxide has drawn attention in the field of energy storage due to the remarkable synergistic effect.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, transition metal hydroxides, [ 12–14 ] oxides, [ 15–19 ] and conductive polymers [ 20–22 ] have been widely employed for energy storage applications. [ 23,24 ] In comparison to the other materials, transition metal hydroxide/oxide has drawn attention in the field of energy storage due to the remarkable synergistic effect.…”
Section: Introductionmentioning
confidence: 99%